Penile Epidermal Inclusion Cyst. (28th May 2012) - El-Shazly, M.; Ghobashy, A.; Allam, A.; Alenezy, T.; Alenezy, N.; Yordanov, E.; Hathout, B.; Albunnai, R.
Abstract : We report a case of epidermal inclusion cyst in a 32-year-old male. This was a complication of circumcision that was neglected over years to form stones and urethrocutaneous fistula. Complete excision of the cyst and repair of the fistula were performed successfully. Histopathological examination confirmed our diagnosis.